System Design Of Course Scheduling Of Telecommunication Engineering Majors At State Polytechnic Of Semarang - Amin Syarifuddin (Politeknik Negeri Semarang, 2017)
Telecommunication Engineering is one of Study Program (Prodi) at State Polytechnic of Semarang (Polines). The development of information technology (IT) can provide ease to meet various information needs. Course schedule used as a reference for teaching and learning activities to fit the target. In Prodi Telecommunication Engineering Polines to create a schedule still using Microsoft Excel applications as well as in publications on lecturers and students are still using physical mading. With that background then the authors make the information system scheduling courses. This information system is created using the PHP programming language utilizing the Laravel framework and MySQL database. After the system is completed the test is done by using the black box method to prove all the features work well in accordance with their respective functions. Design model using modeling Use Case Diagram and Entity Relationship Diagram (ERD) can be done to design Scheduling System Subject Telecommunication Engineering Program Polines. This application is made in the form of websites and integrated with the database, so it can be accessed by the user in realtime on the Intranet network. Schedule preparation courses can be done Kaprodi using web-based information system. The results of this information system can be used to create course schedules and can be accessed so that lecturers and students can view the course schedule